SCHOOL-BASED ASSESSMENT PRACTICES AMONG PRIMARY SCHOOL MATHEMATICS TEACHERS BASED ON TEACHING EXPERIENCE - Muhammad Sofwan Mahmud, Muhamad Farhan Abdul Halim, Nadia Fasha Mohd Drus (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
School-based assessment (SBA) is part of a transformation of the Malaysian education system that is used to interpret the academic and non-academic fields as well as to empower teachers to carry out a school-based formative and summative assessment. This study was therefore conducted to identify the use of SBA among elementary school mathematics teachers. Approximately 37 mathematics teachers (12 males and 25 females) were selected to become a sample of this analysis in a district in Malaysia. This study was carried out using the survey method and a questionnaire was used during the data collection process. To answer research questions, the findings of this study were analyzed through descriptive statistical analysis and inferential statistical analysis. Based on the study, the overall mean score of SBA practice among elementary mathematics teachers was strong. However, it was found that there was no significance difference between SBA and teaching experiences based on the results of a one-way ANOVA test. This research furthers SBA and serves as a guide for other mathematical teachers in their respective schools.